1980
DOI: 10.1902/jop.1980.51.10.599
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Destruction Due to Overhanging Amalgam in Periodontal Disease

Abstract: Interproximal bone loss around 100 teeth with overhanging amalgam restorations was measured and compared to interpoximal bone loss around 100 contralateral teeth without overhanging amalgams. The latter served as controls. Overall, bone loss was found greater around teeth with overhangs (P < 0.01). This finding was true for all periodontal disease types. However, the more severe the periodontal disease the greater the role of the overhang appeared. Small overhangs, unlike medium and large overhangs, did not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 10 publications
0
38
0
1
Order By: Relevance
“…The immense advances in dental treatment have led to use of numerous medicaments and materials in various dental specialities. There have been reported cases in the literature exhibiting irreparable damage to soft and hard tissues of the dental apparatus [1][2][3] when these therapeutic foreign materials are not used within the confinements of the dental structures. Among such materials, dental amalgam is well known and widely applicable restoration for the posterior teeth; with its reported disadvantages when not placed correctly within the boundaries of the prepared cavity [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immense advances in dental treatment have led to use of numerous medicaments and materials in various dental specialities. There have been reported cases in the literature exhibiting irreparable damage to soft and hard tissues of the dental apparatus [1][2][3] when these therapeutic foreign materials are not used within the confinements of the dental structures. Among such materials, dental amalgam is well known and widely applicable restoration for the posterior teeth; with its reported disadvantages when not placed correctly within the boundaries of the prepared cavity [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, careful technique skills and accurate therapy if not provided with these materials, may lead to unfavourable sequelaes [6,7]. The universally used amalgam might cause such a great destruction of bone reminds us to use these materials cautiously and this also recalls the toxicity as regards to other materials which when comes in direct contact with bone could considerably harm it [1].…”
Section: Discussionmentioning
confidence: 99%
“…3,65,66 Tooth roughness can occur secondary to developmental problems (such as enamel hypocalcification) or tooth trauma (such as attrition, abrasion, or fracture; see above). In addition, iatrogenic causes (such as poor restorations [ Figure 2.16], 21,67 especially overhangs, 68 or lack of/improper polishing following a dental prophylaxis) can have a significant effect on periodontal disease (Figure 2.17). 3,6 These issues can usually be rectified with a properly placed restoration and/or polishing.…”
Section: Factors Within the Oral Cavitymentioning
confidence: 99%
“…Parsell et al 1 suggested that the over hang width did not have a signifi cant influence on the alveolar bone loss. Jeff coat and Howell, 7 however, demonstrated that small overhangs did not cause bone loss compared to medium and large channel was drilled from the buccal to the overhangs. Jannson et al 8 demonstrated lingual side of the first premolar space to A number of studies have demonstrated that the prevalence of overhanging amal gam restorations is high.…”
Section: Introductionmentioning
confidence: 98%